2016
DOI: 10.1186/s12904-016-0137-0
|View full text |Cite
|
Sign up to set email alerts
|

The ‘problematisation’ of palliative care in hospital: an exploratory review of international palliative care policy in five countries

Abstract: BackgroundGovernment policy is a fundamental component of initiating change to improve the provision of palliative care at a national level. The World Health Organisation’s recognition of palliative care as a basic human right has seen many countries worldwide develop national policy in palliative and end of life care. There is increasing debate about what form comprehensive palliative care services should take, particularly in relation to the balance between acute and community based services. It is therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 36 publications
(40 reference statements)
1
68
0
1
Order By: Relevance
“…A good example is provided in thinking about the uncritical assumption in palliative care policy internationally that end-of-life care ‘in the community’ is both desired and achievable for all. 109 We agree with Sutherland and colleagues’ 28 assertion that such an approach is primarily grounded in neoliberal discourses of individualism, framing care as something outside of the market and state responsibilities. It promotes a notion of communities as homogeneous and conflict-free – which any basic intersectional analysis of, say, the recent UK election would show as untrue.…”
Section: Recommendations For Practice and Policysupporting
confidence: 60%
See 1 more Smart Citation
“…A good example is provided in thinking about the uncritical assumption in palliative care policy internationally that end-of-life care ‘in the community’ is both desired and achievable for all. 109 We agree with Sutherland and colleagues’ 28 assertion that such an approach is primarily grounded in neoliberal discourses of individualism, framing care as something outside of the market and state responsibilities. It promotes a notion of communities as homogeneous and conflict-free – which any basic intersectional analysis of, say, the recent UK election would show as untrue.…”
Section: Recommendations For Practice and Policysupporting
confidence: 60%
“… 105 , 108 Finally, the promotion of home dying in palliative care policy assumes people live in housing which can support a good end-of-life experience and have family and whānau who are willing and prepared (including financially prepared) to provide care. 109 In many countries, including New Zealand, the inadequate nature of the housing stock and links with reduced health outcomes are well established. 110 Vulnerably housed – and homeless – people experience particular challenges at end of life, 111 although it must be noted that people in this situation ‘are not passive victims of vulnerability, but [are] highly resilient’.…”
Section: Gender and Place Of Deathmentioning
confidence: 99%
“…It is also important to highlight that a home death did not feature in the top three end of life care priorities for either Māori or non-Māori participants. Such findings lend further weight to the need to revisit normative understandings that a ‘good death’ must occur at home [ 39 ], understandings which permeate palliative care policy internationally (for example, [ 40 – 42 ]. Our participants identified that pain and symptom control, attending to spiritual concerns (for Māori) and ‘getting affairs in order’ (for non-Māori) were more important than the actual place of dying.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that in some cases symptoms cannot currently be managed sufficiently in community settings. The limitation of community based services tends not to be acknowledged in palliative care policy documents which advocate ACP to promote care in the community (Robinson et al 2016). Where community based services are insufficient to manage symptoms of a person who is sick and dying a reduction in hospital deaths may not actually demonstrate an increase in the quality of care suggesting that quality is a contestable concept and numerical measurements about place of care are limited when not linked to clinical data (Sleeman et al 2017).…”
Section: Dnacpr Policymentioning
confidence: 99%